Association between triglyceride-glucose index and risk of kidney stone: a Chinese population-based case–control study - Feng Shi; Lin Zhang; Dingguo Zhang; Dawei Wang (BMJ Open)
Objective To investigate the association between the triglyceride-glucose (TyG) index, a surrogate marker of insulin resistance and the risk of kidney stones (KSs) in a Chinese population.Design Case–control study.Setting Three Physical Examination Centers in Shanghai, China, between January 2020 and December 2022.Participants A total of 117 757 Chinese adults underwent health check-ups during the study period.Primary and secondary outcome measures The association between the TyG index and the risk of KS was assessed using multivariable logistic regression analysis. The dose–response relationship between the TyG index and KS risk was evaluated with a restricted cubic spline (RCS) analysis. Stratified analyses were conducted to explore whether factors such as age, sex, obesity, hypertension and diabetes modify the association between the TyG index and KS risk.Results Out Of the 117 757 participants, 11 645 (9.9%) were diagnosed with KS using ultrasound. Individuals with KS had significantly higher TyG values than controls (p<0.001). The multivariable-adjusted ORs for KS increased across TyG quartiles, with the highest quartile showing an OR of 1.28 (95% CI 1.20 to 1.36) compared with the lowest quartile. Each SD increase in the TyG index was associated with a 10% higher risk of KS (OR: 1.10, 95% CI 1.08 to 1.13). RCS analysis revealed a significant positive and linear association between TyG index and KS (p overall<0.001, p non-linear=0.136). The positive association persisted across the subgroup and sensitivity analyses.Conclusions The TyG index was positively associated with the risk of prevalent KS, suggesting that insulin resistance may be a risk factor for KS in the Chinese population.